Effects of Heat-Treatment on the Microstructure, Electromagnetic Wave Absorbing Properties, and Mechanical Properties of SiCN Fibers - Long, Xin; Zhang, Shuai; Shao, Changwei; Wang, Bing; Wang, Yingde (Frontiers in Materials, 2020)
SiCN fibers can not only be used for reinforcement of composites materials but also for electromagnetic wave (EMW) absorbing applications in a high-temperature oxidizing environment above 1,200°C. In this work, the microstructural evolution and EMW absorbing properties of SiCN fibers after annealing at 1,300–1,600°C in N2 atmosphere were investigated. Results showed that the amorphous SiCN fibers presented poor EMW absorbing properties when the annealing temperature was below 1,400°C. As the annealing temperature increased to 1,500°C, the EMW absorbing properties could been largely enhanced with a minimum reflation loss value of -55.8 dB and an effective absorption bandwidth value of 2.5 GHz. The enhanced EMW absorbing properties should contribute to the formation and growth of grain boundaries and defects among the amorphous fiber matrix and turbostratic graphite carbon, which could enhance the space charge polarization at the heterogeneous interfaces and increase the conductivity of the SiCN fibers. Meanwhile, SiCN fibers retained a rather high tensile strength of ∼1.0 GPa after annealing at 1,500°C, which showed it to be a promising candidate for reinforcing the stealth ceramic matrix composites used in harsh environments.